THE ROLE OF NAGAN RAYA’S REGIONAL DEVELOPMENT PLANNING AGENCY IN INFORMATION DISCLOSURE AND COMMUNICATION TO THE PUBLIC TO ACHIEVE GOOD GOVERNANCE - Ariansyah, Dodi; Maulida, Desi (Transpublika Publisher, 2022)
Good governance has long been practiced by all parties, including the government and society. However, many people do not understand the concept of governance. Returning government control to the people to create an open and participatory government. One of the efforts to make it happen is transparency or disclosure of information to the public. This study aims to determine the efforts of Bappeda Nagan Raya in realizing good governance. This study uses a qualitative method. The types of data used are primary data and secondary data. The focus of this research is 1) participation, 2) transparency, and 3) accountability. Data was collected through interviews, observation, and documentation. The results of this study indicate that Bappeda Nagan Raya has reflected a good government by applying the principles of transparency, accountability and community participation, namely by providing information about government actions, and is responsible for explaining to the public, for example, the reasons behind the action, the form of action and the time and place of action. how to take action, must be available to stakeholders and the wider community. This is not without obstacles, one of the obstacles faced by Bappeda Nagan Raya is the lack of human resources who are fluent in technology. However, there have been efforts as a step to ensure the disclosure of public information during this pandemic, such as providing information through social media or websites that in fact can be accessed by everyone, but not all people understand technology.